2013
DOI: 10.1038/nature12132
|View full text |Cite
|
Sign up to set email alerts
|

Architecture and evolution of a minute plant genome

Abstract: It has been argued that the evolution of plant genome size is principally unidirectional and increasing owing to the varied action of whole-genome duplications (WGDs) and mobile element proliferation1. However, extreme genome size reductions have been reported in the angiosperm family tree. Here we report the sequence of the 82-megabase genome of the carnivorous bladderwort plant Utricularia gibba. Despite its tiny size, the U. gibba genome accommodates a typical number of genes for a plant, with the main diff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

14
292
1
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 301 publications
(308 citation statements)
references
References 25 publications
14
292
1
1
Order By: Relevance
“…Carnivorous plants are interesting model systems not only for understanding the molecular mechanisms underlying nutrient acquisition strategies, but also for discovering the regulatory underpinnings of their unique trapping morphologies. U. gibba is of particular interest given the previous publication of an ∼82-Mb short-read assembly (10), which revealed that its genome gained and deleted gene duplicates significantly faster than those of other genomes (11). Given that the U. gibba genome likely descended via considerable shrinkage from an ancestral genome up to 1.5 Gb in size (12), duplicates that survived deletion during its evolutionary history arguably evolved under greater purifying selection pressure compared with the more expansive genomes of most angiosperms.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Carnivorous plants are interesting model systems not only for understanding the molecular mechanisms underlying nutrient acquisition strategies, but also for discovering the regulatory underpinnings of their unique trapping morphologies. U. gibba is of particular interest given the previous publication of an ∼82-Mb short-read assembly (10), which revealed that its genome gained and deleted gene duplicates significantly faster than those of other genomes (11). Given that the U. gibba genome likely descended via considerable shrinkage from an ancestral genome up to 1.5 Gb in size (12), duplicates that survived deletion during its evolutionary history arguably evolved under greater purifying selection pressure compared with the more expansive genomes of most angiosperms.…”
mentioning
confidence: 99%
“…Utricularia gibba is an aquatic carnivorous plant with an unusually small but highly dynamic nuclear genome that experienced at least two whole-genome duplication (WGD) events during its evolutionary history since divergence from grapevine, tomato, and other species (10). Carnivorous plants are interesting model systems not only for understanding the molecular mechanisms underlying nutrient acquisition strategies, but also for discovering the regulatory underpinnings of their unique trapping morphologies.…”
mentioning
confidence: 99%
“…It was thought that plants have a 'one-way ticket to genome obesity' due to the retention of proliferating transposable elements 21 . However, analysis of carnivorous plants Utricularia gibba (bladderwort, 82 Mb) 22 and Genlisea aurea (corkscrew, 63.6 Mb) 23 provided evidence that almost all intergenic space can be purged. Small genomes also arise from a reduction in gene number as seen in the aquatic monocotyledon Spirodela polyrhiza, which has the fewest predicted protein coding genes at 19,623 (ref.…”
mentioning
confidence: 99%
“…Within the Lamiales, multiple WGD independent from the paleopolyploidy in the Solanales have been described: two or three in the lineage leading to U. gibba (one of which could be shared with M. guttatus) (18), and one in the lineage leading to S. indicum (estimated age similar to tomato) (19). This latter one and the oldest WGD in U. gibba could denote the same event, possibly even shared with the older WGD in the oleaster and ash lineage, or both could be independent ones, partly depending on their phylogenetic relationship (SI Appendix, section 3.2).…”
mentioning
confidence: 99%